The Population of Fungi in Potato Dextrose Media With Energy Sources Cells - Siti Fatimah; Ahmad Syauqi; Ratna Djuniwati Lisminingsih (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
The growth of fungi can be influenced by nutrients is in the environment, With the additional two kinds of nutrients from sugar plant waste of molasses, and waste of the pepaya taken the filtrate. Both of these wastes contain sugar which is needed by fungal microorganisms to grow and reproduce. The fungus Aspergillus niger, Hansenulla sp, Trichoderma viride, and Candida sp have a synergy interaction in a media. This study aims to learn in the growth of fungal cell populations as cell masses in potato dextrose media with the addition of two kinds of nutrients. The method used in this study was a two-population mean test with 2 treatments, namely the first treatment with the addition of sugarcane drops, and the next with the addition of papaya fruit filtrate, consisting of 11 replications, with incubation for 3 days. The analysis used was the T test and the analysis results obtained were significant, which was shown from P> 0.05. The mass of fungi cells in the addition of nutrients from sugar factory waste was greater than that of papaya fruit filtrate waste